Fairness and rights in international criminal procedure - Rigney, Sophie (Edinburgh University Press, 2022)
Through an in-depth critical analysis of procedural decisions at the ICTY and ICC between 2008 and 2018, Rigney shows that there is a clear separation between fairness and rights in practice. She demonstrates tthat fairness is invoked in international criminal law decisions in inconsistent ways that are frequently at odds with defendants' rights.